2019
DOI: 10.3390/app9030401
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Encapsulation of a New Zinc Phthalocyanine Photosensitizer into Polymeric Nanoparticles to Enhance Cell Uptake and Phototoxicity

Abstract: Efforts to enhance the utility of photodynamic therapy as a non-invasive method for treating certain cancers have often involved the design of dye sensitizers with increased singlet oxygen efficiency. More recently, however, sensitizers with greater selectivity for tumor cells than surrounding tissue have been targeted. The present study provides an approach to the modification of the known photosensitizer zinc phthalocyanine (ZnPc), to enhance its solubility and delivery to cancer cells. Targeting a photosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Although some PDT photosensitizers are already commercially available, mostly derived from porphyrins, these light-sensitive molecules have the disadvantage of being slowly eliminated from the body, causing skin photosensitivity [8,39]. Thus, several research studies have recently reported the discovery of new compounds, such as cyanines [40], squaraines [24], chlorins [41] or phthalocyanines [42] which, by appropriate structural modifications, can ideally override the gaps of first-generation photosensitizers [43].…”
Section: Introductionmentioning
confidence: 99%
“…Although some PDT photosensitizers are already commercially available, mostly derived from porphyrins, these light-sensitive molecules have the disadvantage of being slowly eliminated from the body, causing skin photosensitivity [8,39]. Thus, several research studies have recently reported the discovery of new compounds, such as cyanines [40], squaraines [24], chlorins [41] or phthalocyanines [42] which, by appropriate structural modifications, can ideally override the gaps of first-generation photosensitizers [43].…”
Section: Introductionmentioning
confidence: 99%
“…Among these parameters, MTT analysis (cell viability) is an effective and fast method used to determine cytotoxicity in vitro. In various studies using phthalocyanine, MTT analysis has been used to determine cytotoxicity (33,34). In present study as a result of MTT analysis for both cell lines, 12,8 µM concentration was determined as LD50 (Lethal Dose 50) that caused the death of half of the cells.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Mehraban et al [ 38 ] reported the use of PEG- b -PLGA-based nanocarriers to encapsulate new phthalocyanine derivatives. A new derivative of phthalocyanine was obtained by incorporating para-methylbenzyoxy groups in the β-positions of the ZnPc periphery (ZnPcBCH 3 , Scheme 6 ).…”
Section: Phthalocyanine-polymeric Nanoparticle Delivery Systems For Cancer Photodynamic Therapymentioning
confidence: 99%